New advances in catalysts for C9 petroleum resin hydrogenation - Yu, Chong; Huang, Hui; Li, Qianwen; Xu, Ruoyi; Tao, Shiying; Xiao, Xunwen; Luo, YunJie; Fang, Jianghua (2020)
C9 petroleum resin is a thermoplastic polymer produced by polymerization of C9 fraction obtaining from the steam cracking unit, and could be catalytic hydrogenated to remove the ethylenic C=C bond, aromatic ring with improved physical properties. The research progress in the efficiency supported nickel or/and palladium catalysts for C9 petroleum resin hydrogenation was illustrated and reviewed, further development was discussed.